DETERMINAN AUDITOR SWITCHING PADA PERUSAHAAN NON KEUANGAN - Raden Bima Priambardi; Haryanto Haryanto (Diponegoro Journal of Accounting, 2014)
This study aimes to analyze the determinant of auditor switching in non financial firms. This study uses 6 independent variables, these are change in management, financial distress, client size, auditor size, going concern audit opinion, and growth of client companies. This study used a sample of non financial firms listed Indonesia Stock Exchange (IDX) during the period 2009-2012. There were 45 firms in the Indonesian company that meet the criteria as a sample. This study used quantitative and analytical method used logistic regression using SPSS21.Results of this study showed that not all of the variables in this study significantly influence with auditor switching. Only change in management and going concern audit opinion that significantly influence on auditor switching. Other factors examined in this study such as financial distress, client size, auditor size and growth of client firms didn’t significantly influence on auditor switching